Our solar system - Simon, Seymour (New York : Harper, 2014)
Describes the origins and characteristics of the sun, planets, moons, asteroids, meteoroids, and comets, and features full-color photos and spacecraft images.
School Library Journal, October 2014
Horn Book, April 2015
Science Books & Films (A.A.A.S.), May 2015
Includes index.
6.4
K-3
Keywords: Solar system -- Juvenile literature; Planets -- Juvenile literature; Solar system; Planets; Solar system; Planets